5S Your Life: Using an Experiential Approach to Teaching Lean Philosophy. (24th October 2018) - Witt, Christine M.; Sandoe, Kent; Dunlap, Joanna C.
ABSTRACT: Within the Information Systems domain, employers are often dissatisfied with graduates' competence of the necessary technical skills in the area of integrated business processes. However, teaching complex concepts related to integrated business processes—such as the 5S lean philosophy—is particularly challenging. In this article, we describe how Kolb's experiential learning cycle was used to design a direct‐experience project to support students' learning of the 5S lean philosophy. We also share the results of our inquiry into the effectiveness of the project in maximizing students' learning of and ability to apply the 5S lean philosophy. Based on the results of this study, students' knowledge of categories of waste and lean tools and knowledge of 5S steps significantly increased.